2013
DOI: 10.1021/bm401129j
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavior in Normal and Tumor-Bearing Mice of Tobacco Mosaic Virus

Abstract: Viral nanoparticles (VNPs) have shown great potential as platforms for biomedical applications. Before using VNPs for further biomedical applications, it is important to clarify their biological behavior in vivo, which is rare for rod-like VNPs. In this paper, a study of tobacco mosaic virus (TMV), a typical rod-like VNP, is performed on blood clearance kinetics, biodistributions in both normal and tumor-bearing mice, histopathology and cytotoxicity. TMV was radiolabeled with (125)I using Iodogen method for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…The spleen acts as a blood filter in the body, removing and replacing worn out red blood cells, and it is the center of activity in the RES system. Since TMV particles were eliminated from the blood circulation by the RES, the accumulation of excess amount of TMV may cause spleen enlargement and damage . However, normal weight and morphology of the spleen observed from each mouse after the sacrifice indicated that there were no chronic and/or major inflammatory and toxicity reactions in the RES that could cause the spleen enlargement in any group of animals.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The spleen acts as a blood filter in the body, removing and replacing worn out red blood cells, and it is the center of activity in the RES system. Since TMV particles were eliminated from the blood circulation by the RES, the accumulation of excess amount of TMV may cause spleen enlargement and damage . However, normal weight and morphology of the spleen observed from each mouse after the sacrifice indicated that there were no chronic and/or major inflammatory and toxicity reactions in the RES that could cause the spleen enlargement in any group of animals.…”
Section: Discussionmentioning
confidence: 97%
“…In vivo properties, especially any potential toxic effects, need to be taken into account, when developing novel materials for biomedical applications. There have been many studies that reported in vivo characterization including biodistribution and toxicity of different types of viral nanoparticles used in biomedicine . For example, spherical plant viruses, cowpea mosaic virus (CPMV), and cowpea chlorotic mottle virus (CCMV), as well as filamentous bacteriophage M13, showed broad biodistribution throughout the body, predominantly in the liver and the spleen.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations